2023
DOI: 10.1039/d2cc05522h
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer in metal–organic frameworks

Abstract: Metal-organic frameworks (MOFs, also known as porous coordination polymers or PCPs) are a novel class of crystalline porous material. The tailorable porous structure, in terms of size, geometry and function,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 117 publications
(128 reference statements)
0
21
0
Order By: Relevance
“…53,54 Typically, the appropriate N•••O distance for ET is less than 4.0 Å. 12−14, 16,22 In our study, we found that the distances between the carboxylate oxygen atoms and pyridine nitrogen atoms were 3.267−3.327 Å for 1, 3.044−3.904 Å for 2, 3.092− 3.851 Å for 3, and 3.204 and 3.360 Å for 4, which locate at suitable distances for photoinduced ET (Figure 5). Therefore, in this work, due to the strong hydrogen-bonding interactions together with other intermolecular interactions, the hydrogen atom in the coordinated H 2 O delocalizes and approaches the nitrogen atoms of the pyridine derivatives, which facilitates photoinduced ET from the carboxylates in the host to the pyridine derivatives, resulting in the formation of photogenerated radicals, similar to the behavior of viologen molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…53,54 Typically, the appropriate N•••O distance for ET is less than 4.0 Å. 12−14, 16,22 In our study, we found that the distances between the carboxylate oxygen atoms and pyridine nitrogen atoms were 3.267−3.327 Å for 1, 3.044−3.904 Å for 2, 3.092− 3.851 Å for 3, and 3.204 and 3.360 Å for 4, which locate at suitable distances for photoinduced ET (Figure 5). Therefore, in this work, due to the strong hydrogen-bonding interactions together with other intermolecular interactions, the hydrogen atom in the coordinated H 2 O delocalizes and approaches the nitrogen atoms of the pyridine derivatives, which facilitates photoinduced ET from the carboxylates in the host to the pyridine derivatives, resulting in the formation of photogenerated radicals, similar to the behavior of viologen molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed structural analysis was further conducted to identify the possible transfer path for the ET process in these compounds. Previous studies have suggested that photoinduced ET in solid-state viologen compounds generally occurs through a short contact between the pyridinium moiety and an electron donor (D), for instance, N pyridinium ···D, ,, (α-C–H) pyridinium ···D, , and π pyridinium ···π D . , Typically, the appropriate N···O distance for ET is less than 4.0 Å. ,, In our study, we found that the distances between the carboxylate oxygen atoms and pyridine nitrogen atoms were 3.267–3.327 Å for 1 , 3.044–3.904 Å for 2 , 3.092–3.851 Å for 3 , and 3.204 and 3.360 Å for 4 , which locate at suitable distances for photoinduced ET (Figure ). Therefore, in this work, due to the strong hydrogen-bonding interactions together with other intermolecular interactions, the hydrogen atom in the coordinated H 2 O delocalizes and approaches the nitrogen atoms of the pyridine derivatives, which facilitates photoinduced ET from the carboxylates in the host to the pyridine derivatives, resulting in the formation of photogenerated radicals, similar to the behavior of viologen molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The diverse physical and chemical properties of these layered structures, e.g., graphene, transition-metal dichalcogenides (TMDCs), and MXenes, drive their utilization in electronics, catalysis, and biosensing. 3 On the other hand, porous materials such as metal−organic frameworks (MOFs) 4,5 and COFs with structural tunability, high surface areas, and permanent and periodic porosity (with adjustable pore sizes) have emerged as promising materials for a wide range of applications in gas storage and separation, drug delivery, sensing, energy storage, and conversion. 6−15 Benefiting from 2D materials and porous structures, the 2D COFs with an unprecedented diversity of linkers and linkages, welldefined reactive sites, and regular nanochannels manifested alternative pathways for efficient mass and charge transfer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ever since the discovery of graphene, a great deal of research interest has been devoted to the development of 2D materials consisting of unique optical and electrical properties, including superconductivity, high charge carrier mobility, and mechanical flexibility. , The diverse physical and chemical properties of these layered structures, e.g., graphene, transition-metal dichalcogenides (TMDCs), and MXenes, drive their utilization in electronics, catalysis, and biosensing . On the other hand, porous materials such as metal–organic frameworks (MOFs) , and COFs with structural tunability, high surface areas, and permanent and periodic porosity (with adjustable pore sizes) have emerged as promising materials for a wide range of applications in gas storage and separation, drug delivery, sensing, energy storage, and conversion. Benefiting from 2D materials and porous structures, the 2D COFs with an unprecedented diversity of linkers and linkages, well-defined reactive sites, and regular nanochannels manifested alternative pathways for efficient mass and charge transfer. In particular, 2D conjugated COFs add paramount significance owing to extended π-conjugation in the 2D plane and columnar arrays of π–π stacking between successive COF layers through the rational tuning of building blocks . This facilitates the electronic communication via through-bond (in-plane) and through-space (out-of-plane) interactions, respectively, leveraging interesting photophysical and electronic properties to extend their applications in (opto)­electronics, , photo/electro catalysis, organic field-effect transistors (OFET), , chemical sensing, and photodetectors …”
Section: Introductionmentioning
confidence: 99%